Analisis Pengaruh Pandemi COVID-19 terhadap Transportasi Udara pada Maskapai Susi Air - Thoharoh, Shinta; Albanna, Faiz (CV. Publikasi Indonesia, 2022)
During the COVID-19 pandemic, Susi Air as an airline service company experienced a decrease in the number of passenger flights and cargo flights. This study aims to determine the effect of COVID-19 on the number of passenger and cargo flights and the way Susi Air has stabilized the number of flights during the COVID-19 pandemic. The method in this study uses a combined method or mixed methods. This study uses two types of data, namely primary data in the form of observation data carried out directly by researchers in the field, and secondary data in the form of time series data on the number of passenger flights and cargo flights of Susi Air Airlines at Nusawiru Cijulang Airport and interview data conducted with two operational staff. Susi Air Airlines. The results of the study show that the COVID-19 pandemic affects the number of passenger flights with Susi Air Airlines with a significance value in the run test, which is 0.000, the COVID-19 pandemic affects the number of Susi Air cargo flights with a significance value in the t test, namely amounting to 0.000, as well as the way Susi Air has stabilized the number of flights during the COVID-19 pandemic, namely by utilizing Instagram social media as a promotional tool, conducting ticket sales cooperation through the Traveloka platform, establishing pioneering flight collaborations between Susi Air Airlines and the Provincial Government. , providing discounts on airline ticket prices, and providing Charter Medical Evacuation (Medevac Emergency Indonesia) services as one of its service products.